Shifting Strands Curriculum Theory for a Democratic Age - Griffith, Bryant (SensePublishers, 2012)
In this the sixth book of a series of exploratory and cautionary tales, Griffith revisits the sites of reflective knowledge and practical experiences that have been our historical presuppositions, and which are now in the process of flux and change. As in his previous books, historical discourse, what we know and can know about the past, is used as the baseline for understanding. This is an ongoing process, where ideas are considered, used to interact with other ideas, and then, among communities of learners, are incorporated, supplanted, or rejected. This is more than a dialectical process because it is based in human action. In education, broadly speaking, we have taught and have learned that this was a linear, rational path that could be mapped, but in today's fragmented, decentered world of difference we can no longer be certain that our presuppositions hold or apply. Using the analogy of shifting strands, this book provides a way of coming to understand, rather than a way of knowing. It suggests that our emerging paradigm will be grounded in presuppositions that are relative to person, place, and time and that certainty may be illusive. The role of introducing ideas like these in a mass capitalist democracy such as ours is a staggering challenge, and it is one that has fallen to educators whether they wish it or not. Shifting Strands challenges both teachers and learners to take up the torch and run with it. This can be accomplished by thinking in a way that is both historical and philosophical; one that understands that learning occurs when we understand where our learners are situated in terms of place and thought. Thinking and knowing about the world is relative to who you are and your ability to thinking in a critical and reflexive way. This is only the first part of the challenge. The second, and no less important, task is for you to realize the power of our polymodal world. Increasingly, we rely on social networks in our decision-making and retreat from the more difficult process of negotiation and interaction, but it is this process that schooling must explore and practice. Our world is paradoxical. There are few, if any, certainties and the trip to understanding our reasons for believing and acting as we do is one with many different routes. It is an exciting time, full of possibility and open to the maverick in you, and open to your creative spirit. Come along for the ride.
Keywords: Education; Education, general; Education (general)